1999
DOI: 10.1200/jco.1999.17.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid Tumor: Prognostic Factors and Outcome After Surgery, Radiation Therapy, or Combined Surgery and Radiation Therapy

Abstract: Wide local excision with negative pathologic margins is the treatment of choice for most desmoid tumors. Function-sparing resection is appropriate because adjuvant radiation therapy can offset the adverse impact of positive margins. Unresectable disease should be treated with definitive radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
366
4
20

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(412 citation statements)
references
References 32 publications
22
366
4
20
Order By: Relevance
“…Local infiltrative growth and tissue invasion can result in pain, deformity, functional impairment, and death when vital organs are involved. 14,16,17 The attendant morbidity and mortality from these tumors is highly sitedependent. Intraabdominal desmoid infiltration of vital organs reportedly leads to a 10-year mortality rate of approximately 37%.…”
Section: Results Both Patients Demonstrated Ongoing Radiographic Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Local infiltrative growth and tissue invasion can result in pain, deformity, functional impairment, and death when vital organs are involved. 14,16,17 The attendant morbidity and mortality from these tumors is highly sitedependent. Intraabdominal desmoid infiltration of vital organs reportedly leads to a 10-year mortality rate of approximately 37%.…”
Section: Results Both Patients Demonstrated Ongoing Radiographic Andmentioning
confidence: 99%
“…19 Adjuvant radiotherapy has been shown to reduce recurrence rates by as much as 50%, and may offset the negative prognostic impact of positive surgical margins, allowing for a surgical approach that balances local control with a significant impact on long-term function and morbidity. 16 Despite having a relatively high local failure rate, surgical resection of extraabdominal desmoid tumors, with adjuvant radiotherapy for a positive surgical margin, remains the standard approach. Although primary radiotherapy can produce local control rates that are comparable to those achieved with surgery alone, 25 the risk of secondary malignancy and the potential for postradiation fibrosis make surgery the initial option of choice if a negative surgical margin resection is anticipated.…”
Section: Results Both Patients Demonstrated Ongoing Radiographic Andmentioning
confidence: 99%
“…Nevertheless, it must be noted that the importance of positive margin status to local recurrence rates, is still a matter of debate. In contrast to other published series [2,10], a study by Gronchi et al showed that presence of microscopic disease did not affect long-term disease-free survival in patients with primary presentation of extra-abdominal desmoid tumors [11]. Primary RT is an appropriate alternative for patients who are not good surgical candidates [12].…”
Section: Discussionmentioning
confidence: 97%
“…Given the benign nature of these tumors, treatment strategies aim at achieving local control while preserving proper function and providing with an adequate cosmetic result [4]. When medically and technically feasible, complete resection of the tumor with negative microscopic margins is the first-line treatment [10]. Nevertheless, it must be noted that the importance of positive margin status to local recurrence rates, is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,21 Wide surgical excision offers the best chance of avoiding recurrence but is difficult to achieve because of the infiltrative nature of desmoid tumors. 2 Spontaneous disappearance of desmoid tumors has occasionally been reported. 5,11 In the current report, the owner declined treatment.…”
mentioning
confidence: 99%